Amikacin liposome inhalation suspension clinical benefit–risk assessment for refractory Mycobacterium avium complex lung disease. Issue 3 (11th July 2022) - Marras, Theodore K.; Hassan, Mariam; Mange, Kevin C.; Ciesielska, Monika; Murthy, Shilpa Dhar; Jumadilova, Zhanna; Chatterjee, Anjan
Mycobacterium avium complex (MAC) is the leading cause of nontuberculous mycobacterial lung disease, which can be associated with progressive lung damage and increased mortality [1]. Patients with MAC lung disease have substantial disease burden and limited treatment options [1]. Up to 40% of patients experience failure, with lengthy multidrug treatments, relapse or reinfection [2]. For patients with treatment-refractory MAC lung disease (persistent MAC-positive sputum despite ≥6 months of guideline-based therapy (GBT)), international guidelines recommend the addition of amikacin liposome inhalation suspension (ALIS) to GBT regimens [3]. In clinical trials, patients with treatment-refractory MAC lung disease had improved culture conversion with ALIS+GBT versus GBT [4, 5]. Marras et al . report a low number needed to treat and high number needed to harm supporting addition of amikacin liposome inhalation suspension to guideline-based treatments in patients with treatment-refractory Mycobacterium avium complex lung disease https://bit.ly/3tPFW7D